Association Between Endogenous Testosterone and Cerebrovascular Disease in the ARIC Study (Atherosclerosis Risk in Communities). Issue 11 (November 2016) - Srinath, Reshmi; Gottesman, Rebecca F.; Hill Golden, Sherita; Carson, Kathryn A.; Dobs, Adrian
Abstract : Background and Purpose—: Epidemiological studies in men suggest a relationship between endogenous testosterone and ischemic vascular events. We hypothesized that low testosterone is independently associated with ischemic stroke and ischemic brain changes. Methods—: In 1558 male participants (mean [SD] age, 63.1 [5.6] years; body mass index, 28.2 [4.3] kg/m 2 ) from visit 4 (1996–1998) of the ARIC study (Atherosclerosis Risk in Communities) without cardiovascular disease, stroke, and previous testosterone therapy, we measured plasma total testosterone by liquid chromatography mass spectrometry using morning samples and divided levels into tertiles (median [25th–75th percentile], 377.6 [288.4–480.1] ng/dL). General linear models, for cross-sectional analyses, and proportional hazards regression, for time-to-event analysis, examined the association of testosterone with participant characteristics and incident stroke through 2011. Linear and logistic regression models examined the association of testosterone with percentage white matter hyperintensities and prevalent infarcts in participants (n=257) who underwent brain magnetic resonance imaging at visit 5 (2011–2013). Analyses were adjusted for age, race, and ARIC center, body mass index, waist circumference, smoking status, diabetes mellitus, hypertension, low-density lipoprotein, and high-density lipoprotein. Results—: Lower testosterone was significantly associated with higher body mass index, greater waist circumference, diabetes mellitus, hypertension, lower high-density lipoprotein, and never smoking. After adjustment, no association of testosterone with incident stroke was found (hazard ratios [95% confidence intervals] for tertile 1 or 3 versus 2, 1.47 [0.83–2.61], 1.15 [0.62–2.14]; median follow-up, 14.1 years), nor with percentage white matter hyperintensities, cortical infarcts, or subcortical infarcts. Conclusions—: After controlling for atherosclerotic risk factors, there was no association between endogenous testosterone and incident clinical stroke or ischemic brain changes in community-dwelling men.